Sectoral Financing Concentration and Profitability of Islamic Banking in Indonesia - Agus Widarjono; M.B. Hendrie Anto; Sahabuddin Sidiq (Share: Jurnal Ekonomi dan Keuangan Islam, 2022)
This paper investigates the extent to which sectoral financing concentration affects the Islamic banks' profitability in Indonesia. As additional control variables, we include bank-specific and macroeconomic conditions. This study utilizes the aggregated financial statements of Islamic banks in Indonesia from January 2010 through December 2019 and analyzed with the Autoregressive distributed lag (ARDL) model. The results confirm cointegration evidence, demonstrating the long-term relationship between the dependent and independent variables. The results clearly indicate that sectoral financing concentration increases the profitability of Islamic banks. Furthermore, excessive financing and high non-performing financing reduce the profitability of Islamic banks. As a financial sector, Islamic banks' performance is contingent on favorable economic and macroeconomic conditions, such as high economic growth and low inflation. These findings imply that Islamic banks must employ skilled workers who are experts in related economic sectors, which is one of the primary goals of Islamic bank financing.========================================================================================================== ABSTRAK – Konsentrasi Pembiayaan Sektoral dan Profitabilitas Bank Syariah di Indonesia. Tulisan ini mengkaji sejauh mana konsentrasi pembiayaan sektoral mempengaruhi profitabilitas bank syariah di Indonesia. Sebagai variabel kontrol tambahan, kami menyertakan kondisi spesifik bank dan variabel makroekonomi. Penelitian ini menggunakan agregat laporan keuangan bank syariah di Indonesia dari Januari 2010 sampai Desember 2019 dan dianalisis dengan model Autoregressive distributed lag (ARDL). Hasil kajian mengkonfirmasi bukti kointegrasi, yang menunjukkan hubungan jangka panjang antara variabel dependen dan independen. Hasil kajian memperjelas bahwa konsentrasi pembiayaan sektoral dapat meningkatkan profitabilitas bank syariah, sementara pembiayaan yang berlebihan dan pembiayaan bermasalah yang tinggi mengurangi profitabilitas bank syariah. Sebagai institusi yang bergerak di sektor keuangan, kinerja bank syariah sangat bergantung pada kondusifitas sistem ekonomi dan kondisi makroekonomi, seperti pertumbuhan ekonomi yang tinggi dan inflasi yang rendah. Temuan ini menyiratkan bahwa bank syariah harus mempekerjakan pekerja terampil yang ahli di sektor ekonomi terkait, yang merupakan salah satu tujuan utama pembiayaan bank syariah.